Innovations to improve access to musculoskeletal care. Issue 5 (October 2020) - Chehade, Mellick J.; Yadav, Lalit; Kopansky-Giles, Deborah; Merolli, Mark; Palmer, Edward; Jayatilaka, Asangi; Slater, Helen
Abstract: Innovation is a form of realising a new way of doing something, often ignoring traditional wisdom, in order to meet new challenges. Globally, particularly in emerging economies, the high burden of musculoskeletal conditions and their contribution to multimorbidity continue to rise, as does the gap for services to deliver essential care. There is a growing need to find solutions to this challenge and deliver person-centred and integrated care, wherein empowering patients with the capacity for self-management is critical. Whilst there is an abundance of information available online to support consumer education, the number of sources for credible medical information is diluted by uninformed anecdotal social media solutions. Even with the provision of high-quality information, behavioural change does not necessarily follow, and more robust educational approaches are required. In this chapter, we examine innovation, its management and the strategic directions required to improve musculoskeletal healthcare at macro (policy), meso (service delivery) and micro (clinical practice) levels. We discuss the critical role of consumer agency (patients and their families/carers) in driving innovation and the need to leverage this through empowerment by education. We provide a snapshot of real-world examples of innovative practices including capacity building in consumer and interprofessional musculoskeletal education and practice; recommendations to transform the access and delivery of integrated, person-centred care; and initiatives in musculoskeletal care and implementation of models of care, enabled by digital health solutions including telehealth, remote monitoring, artificial intelligence, blockchain technology and big data. We provide emerging evidence for how innovation can support systems' strengthening and build capacity to support improved access to 'right' musculoskeletal care, and explore some of the ways to best manage innovations. We conclude with recommended systematic steps to establish required leadership, collaboration, research, networking, dissemination, implementation and evaluation of future innovations in musculoskeletal health and care.